Pop-Up Structures and the Fracture Pattern in the Balsam Lake Area, Southern Ontario - Rutty, Andrea; Cruden, Alexander (Géographie physique et Quaternaire)

(untitled) (Les Presses de l'Université de Montréal, 1993)
ABSTRACTAn examination of topographic lineaments detectable in Landsat TM images and measurement of joints in outcrop in the Balsam Lake area reveals a systematic bedrock fracture pattern with three principal sets oriented 091°, 027°, and 152°. The 027° trend is parallel to a major aeromagnetic anomaly, the Niagara-Pickering Linear Zone (NPLZ), which underlies the Balsam Lake area and is thought to mark the sub-Paleozoic continuation of the Proterozoic Central Metasedimentary Belt Boundary Zone (CMBBZ). Possible origins of the main joint sets due to Acadian (091° set), Alleghanian (152° set) and St. Lawrence rift system tectonics (091° and 027° sets) are discussed. En-echelon pop-up structures have a mean principal trend of 118°. They displace Lake Algonquin paleobeaches, suggesting formation less than 12,500 years ago. The orientation of the pop-up structures is subnormal to the current in situ maximum horizontal stress direction, SHmax (020°), and is parallel to members of the 091° joint set, indicating possible nuclea-tion on favourably-oriented pre-existing joints. These pop-ups are the only features in the Balsam Lake area with strong evidence for a neotectonic age.